2003
DOI: 10.1093/arclin/18.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a web-based neuropsychological test protocol for sports-related return-to-play decision-making

Abstract: The Concussion Resolution Index (CRI) is an online assessment tool designed to track resolution of symptoms following sports-related concussion. The CRI is composed of six subtests measuring reaction time, visual recognition, and speed of information processing. Three factors are derived from the subtests: Simple Reaction Time (SRT), Complex Reaction Time (CRT), and Processing Speed (PS). Multiple alternate forms within subtests afford simple, reliable, assessment of change, relative to a baseline test complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 0 publications
1
29
0
3
Order By: Relevance
“…In addition, their findings were similar to ours when using a longer testretest time interval and the same test form. 8,9,21 We controlled for random error by testing individuals at approximately the same time of day; testing in the same environment; and following a standardized testing procedure, using the ImPACT manufacturer's instructions and controlling for effort. Although we accounted for sources of random error, systematic error may have influenced our results through hardware and software applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, their findings were similar to ours when using a longer testretest time interval and the same test form. 8,9,21 We controlled for random error by testing individuals at approximately the same time of day; testing in the same environment; and following a standardized testing procedure, using the ImPACT manufacturer's instructions and controlling for effort. Although we accounted for sources of random error, systematic error may have influenced our results through hardware and software applications.…”
Section: Discussionmentioning
confidence: 99%
“…6 Randolph et al 6 reviewed the psychometric properties of computerized neuropsychological testing platforms and found limited to no evidence of reliability and validity for all existing computerized platforms. Several groups [6][7][8][9][10] investigating the reliability of the ImPACT (ImPACT Applications, Pittsburgh, PA) have found intraclass correlation coefficients (ICCs) ranging from 0.15 to 0.85 for any 1 outcome measure. Specifically, higher ICCs (0.38 to 0.85) were reported for the ImPACT composite visual motor speed and composite reaction time scores and lower ICCs (0.23 to 0.64) for composite visual and verbal memory.…”
mentioning
confidence: 99%
“…[76][77][78][79][80][81][82][83][84] One critique of the computerized tests is that the vast majority of studies have been conducted by the developers of the tests, which raises some concern for bias, because some independent study results have suggested slightly less reliable results. 85,86 A few of these computerized tests have been widely adopted at all levels of sport participation.…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…The CSI also employs a traditional continuous performance test format in computerized form to measure attention, response speed, and multitasking (executive function) [12]. The CSI provides rapid and repeatable neurocognitive screenings with instantly accessible results.…”
Section: Stability Indexmentioning
confidence: 99%
“…Based on preliminary data, the modalities chosen were computerized formats of eyetracking, balance and stability, and neurocognitive assessments. While all three modalities have been individually validated as being able to distinguish between concussed and nonconcussed populations [10][11][12][13], the goal of this study was to examine the enhancement in individual test discriminatory capability through the combination of all three assessment modality scores into a single, integrated multimodal system score. A secondary goal of the research was to assess the feasibility of developing a field-deployable system, with the compressed assessment, score compilation time, and portability that this application requires.…”
Section: Introductionmentioning
confidence: 99%